Obstetric brachial plexus injuries (OBPIs): health-related quality of life in affected adults and parents - Yau, Christopher W. H. (Health Qual Life Outcomes, 2018)
BACKGROUND: Obstetric brachial plexus injuries (OBPIs) are rare but can have significant implications for those affected, their caregivers and the health system. Symptoms can range from restricted movement to complete paralysis of the arm. We investigated health-related quality of life in adults with OBPIs and parents of children with permanent OBPIs, compared these with population norms, and investigated whether certain socio-demographic or clinical factors were associated with the quality of life in these cohorts. METHODS: A cross-sectional study examined 50 affected adults and 78 parents. Participants completed EQ-5D-5 L and characteristics questionnaires. EQ-5D-5 L responses were mapped onto an EQ-5D-3 L value set to generate utility scores. Mean utility scores were compared with English population norms. Univariable and multivariable linear regression models were conducted to assess for associations between participant characteristics and the utility scores. RESULTS: The overall mean utility scores for affected adults and parents were 0.56 (SD 0.28) and 0.80 (SD 0.19) respectively. Affected adults (95% CI (− 0.38, − 0.22), p < 0.001) and parents of children with permanent OBPIs (95% CI (− 0.10, − 0.02), p = 0.007) had lower mean utility scores, and therefore quality of life, compared to English population norms. For affected adults, previous OBPI surgery (95% CI (0.01, 0.25), p = 0.040), employment in non-manual work (95% CI (0.06, 0.30), p = 0.005) and having a partner (95% CI (0.04, 0.25), p = 0.009) appeared to be positively associated with the utility score. Affected adults receiving disability benefits related to OBPIs appeared to have worse utility scores than those not receiving any disability benefits (95% CI (− 0.31, − 0.06), p = 0.005). For parents, employment was associated with better utility scores (95% CI (0.02, 0.20), p = 0.024) but the presence of one or more medical condition appeared to be associated with worse utility scores (95% CI (− 0.16, − 0.04), p = 0.001). CONCLUSIONS: Adults with OBPIs and parents of children with permanent OBPIs reported worse utility scores, and therefore quality of life, compared to the English general population. We also identified certain characteristics as possible factors to consider when dealing with utility scores in these cohorts. The utility scores in this study can be used in future economic evaluations related to OBPIs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12955-018-1039-z) contains supplementary material, which is available to authorized users.